2017
DOI: 10.1093/mnras/stx2323
|View full text |Cite
|
Sign up to set email alerts
|

The large-scale environment from cosmological simulations – I. The baryonic cosmic web

Abstract: Using a series of cosmological simulations that includes one dark-matter-only (DM-only) run, one gas cooling-star formation-supernovae feedback (CSF) run and one that additionally includes feedback from active galactic nuclei (AGNs), we classify the large-scale structures with both a velocity-shear-tensor code (Vweb) and a tidal-tensor code (Pweb). We find that the baryonic processes have almost no impact on large-scale structures -at least not when classified using aforementioned techniques. More importantly,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 80 publications
2
43
0
Order By: Relevance
“…The large-scale environmentof the whole simulation box has been classified into knots, filaments, sheets, and voids using two algorithms: VWEB, which uses a velocity-shear-tensor, and PWEB , which uses a tidal-tensor (Cui et al (2018(Cui et al ( , 2019. These algorithms are described in Section 2.2, and their resolution and threshold setting are further discussed in Appendix Section B.…”
Section: E T H O D Smentioning
confidence: 99%
See 2 more Smart Citations
“…The large-scale environmentof the whole simulation box has been classified into knots, filaments, sheets, and voids using two algorithms: VWEB, which uses a velocity-shear-tensor, and PWEB , which uses a tidal-tensor (Cui et al (2018(Cui et al ( , 2019. These algorithms are described in Section 2.2, and their resolution and threshold setting are further discussed in Appendix Section B.…”
Section: E T H O D Smentioning
confidence: 99%
“…Here, we apply two algorithms, VWEB and PWEB , to classify the largescale environmentof the whole simulation box into knots, filaments, sheets, and voids (Cui et al 2018(Cui et al , 2019.…”
Section: The Cosmic Webmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last two decades, the analysis of cosmological hydrodynamical simulations has shown that a large fraction of these "missing baryons" 1 may reside in a shockheated phase of the IGM with gas densities ρ 50ρcritΩ b and temperatures 10 5 K < T < 10 7 K (Cen & Ostriker 1999;Davé et al 1999;Cen et al 2001;Davé et al 2001;Kang et al 2005;Cen & Ostriker 2006;Davé & Oppenheimer 2007); such a phase is usually denominated Warm-Hot Intergalactic Medium (WHIM). Based on these results from simulations, a variety of methods to directly detect the missing baryons has been proposed in the literature, e.g., via future radio surveys (Araya-Melo et al 2012;Vazza et al 2016;Horii et al 2017;Cui et al 2018), UV spectroscopy (Oppenheimer & Davé 2009;Bertone et al 2010;Tepper-García et al 2011;Nelson et al 2018c) and X-ray spectroscopy (Phillips et al 2001;Yoshikawa et al 2003;Viel et al 2005;Branchini et al 2009;Takei et al 2011;Kaastra et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…where λ th is a free threshold parameter Libeskind et al 2012Libeskind et al , 2013. Following the discussion of Carlesi et al (2014); Cui et al (2018Cui et al ( , 2019, we set λ th = 0.1, which presents better agreement to the visualised density field. Our mock galaxies are then placed onto the same grid checking for the web classification of the cell they lie in.…”
Section: A the Vweb Methodsmentioning
confidence: 99%